Proteolysis and membrane capture of F-spondin generates combinatorial guidance cues from a single molecule - Zisman, Sophie (The Rockefeller University Press, 2007)
The formation of neuronal networks is governed by a limited number of guidance molecules, yet it is immensely complex. The complexity of guidance cues is augmented by posttranslational modification of guidance molecules and their receptors. We report here that cleavage of the floor plate guidance molecule F-spondin generates two functionally opposing fragments: a short-range repellent protein deposited in the membrane of floor plate cells and an adhesive protein that accumulates at the basement membrane. Their coordinated activity, acting respectively as a short-range repellant and a permissive short-range attractant, constricts commissural axons to the basement membrane beneath the floor plate cells. We further demonstrate that the repulsive activity of the inhibitory fragment of F-spondin requires its presentation by the lipoprotein receptor–related protein (LRP) receptors apolipoprotein E receptor 2, LRP2/megalin, and LRP4, which are expressed in the floor plate. Thus, proteolysis and membrane interaction coordinate combinatorial guidance signaling originating from a single guidance cue.